Evaluation of bioactive compounds from Sapodilla (Manilkara zapota) peel and seeds obtained by ultrasound-assisted technique (Research, Society and Development, 2020)
Sapodilla is an exotic fruit consumed in several countries, which generates a significant amount of waste which can be used as a source of bioactive compounds. In this context, this work aimed to extract bioactive compounds from sapodilla peel and seeds through an ultrasound-assisted technique. This work is an explanatory quantitative research based on laboratory experiments. Extraction was carried out with distilled water, methanol and ethanol at concentrations between 40% and 80%, subjected to ultrasound for 1 h. The highest levels of phenolic compounds were obtained in 40% methanol peel extract (126.0 mg GAE/100 g of residue) and in 80% methanol seed extract (65.3 mg GAE/100 g of residue). In relation to total flavonoids, the highest levels were found in 80% ethanol peel extract (90.0 mg QCE/100 g) and in 80% ethanol seed extract (33.3 mg QCE/100g). The highest antioxidant activity for these extracts was obtained by the ABTS method, around 700.0 μM Trolox/g of residue. Seven polyphenolic compounds were identified and quantified by HPLC, with gallic acid being the major compound, followed by epigallocatechin and catechin. The ultrasound technique was efficient for obtaining bioactive extracts of sapodilla residues with potential for future application as a natural source of bioactive compounds.